La necesidad de reformar el art. 202 del Código de la Niñez y Adolescencia a fin de implementar dentro juntas cantonales de protección del derecho del menor, sanciones para la explotación del trabajo infantil a fin de garantizar los derechos prioritarios de los niños, niñas y adolescentes - Chimbo Córdova, Richard Fauricio (2015)
The State must ensure legal certainty. Children and adolescents. Through eradication and punishment of child labor, generating reforms Art. 202 of the Code of Childhood and Adolescence to implement within Cantonal Boards Juvenile Protection Law, penalties for child labor exploitation thereby safeguarding its development moral and material. The principles of priority and higher interest should ensure effectiveness in the eradication and punishment of child labor, creating a security framework against these acts which infringe the rights of the child. Cantonal Boards for Protection of the Rights of Children and Adolescents should ensure priority and higher interest through eradication and punishment of child labor The eradication and punishment of child labor, guaranteeing the rights of priority and higher interest authorities Cantonal Boards for Protection of Child Rights, to contribute material and equipment of children and adolescents development through eradication and punishment of child labor